2018
DOI: 10.3390/nu10121976
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index is Strongly Associated with Hypertension: Results from the Longevity Check-Up 7+ Study

Abstract: The present study was undertaken to provide a better insight into the relationship between different levels of body mass index (BMI) and changing risk for hypertension, using an unselected sample of participants assessed during the Longevity Check-up 7+ (Lookup 7+) project. Lookup 7+ is an ongoing cross-sectional survey started in June 2015 and conducted in unconventional settings (i.e., exhibitions, malls, and health promotion campaigns) across Italy. Candidate participants are eligible for enrolment if they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
102
0
16

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(138 citation statements)
references
References 47 publications
20
102
0
16
Order By: Relevance
“…Our results are consistent with most previous studies that showed that the risk of hypertension increases with rising BMI [14,19]. The "Look up 7+" epidemiological study showed that blood pressure increased signi cantly across BMI levels [20], which indicated that there was not only a strong relationship between BMI and hypertension, but also an association between the continuous variables of BMI and blood pressure. Our study con rmed that there was a nonlinear dose-response relationship between BMI and the risk of hypertension, which was similar to previous studies [21,22].…”
Section: Discussionsupporting
confidence: 92%
“…Our results are consistent with most previous studies that showed that the risk of hypertension increases with rising BMI [14,19]. The "Look up 7+" epidemiological study showed that blood pressure increased signi cantly across BMI levels [20], which indicated that there was not only a strong relationship between BMI and hypertension, but also an association between the continuous variables of BMI and blood pressure. Our study con rmed that there was a nonlinear dose-response relationship between BMI and the risk of hypertension, which was similar to previous studies [21,22].…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with previous mortality analyses based on NHANES data . However, we suggest that these metrics may be actual contributors to the other four factors such that if these three metrics are also addressed, they will indeed have an indirect effect on mortality …”
Section: Discussionmentioning
confidence: 99%
“…Adjusted for age, sex, race/ethnicity, income, college degree, family history of CVD, BMI, smoking status, physical activity, healthy diet score, total cholesterol, blood pressure, and HbA1c level. metrics may be actual contributors to the other four factors such that if these three metrics are also addressed, they will indeed have an indirect effect on mortality 37,38. The strengths of our study include its large, nationally representative sample of the US adults with mortality status after up to 27 years of follow-up.…”
mentioning
confidence: 99%
“…However, the prevalence of overweight and obesity was greater in hypertensive participants. According to Landi et al [24], body index mass is closely related to hypertension as a cause of this disease and may have a direct effect on blood pressure, independent of other clinical risk factors. In the study population, this is certainly due to non-compliance with the nutrition and hygienic measures that patients should comply with.…”
Section: Discussionmentioning
confidence: 99%